The Freedom of Assembly and Association under the ECHR with Special Regard to Central Europe - Tubić , Bojan (The ECHR at 70: The Central European Narrative, 2025)
The freedom of assembly and association represents one of the foundations of every democratic society. State authorities have a duty to take all adequate measures in relation to lawful demonstrations or other forms of assembly in order to ensure their peaceful organisation and the security of citizens. The freedom of association also includes the right to form, join and refuse to join an organisation. This freedom is realized through political parties, trade unions, minority organisations, etc. These freedoms are not absolute and the States may impose certain restrictions on their enjoyment. These restrictions must be prescribed by law, which is necessary in a democratic society, and they must pursue a legitimate aim. The restrictions can be imposed for the protection of public order, rights and interests of others and they must be proportionate to the aims pursued. Moreover, these freedoms are closely related to other rights and freedoms enshrined in the Convention, like the freedom of expression, which also have a significant role in modern democratic societies.Keywords: freedom of assembly, freedom of association, ECHR, human rights